Primary splenic angiosarcoma: a case series of a rare oncological entity and diagnostic challenge - Iris Dirven; Philippe Leclercq; Lionel D'Hondt; Valentine Delmotte; Pierre Lefesvre; Hendrik Reynaert; Frederik Vandenbroucke; Magali Surmont (Acta Oncologica, 2024)
Background and purpose: Primary angiosarcoma of the spleen (PAS), an exceptionally rare and aggressive neoplasm with high metastatic risk (70%–85%), is frequently diagnosed in an advanced or metastatic stage. It presents diagnostic challenges due to its nonspecific symptomatology and resemblance to benign vascular lesions in various imaging modalities.